Reproduction of Palmistichus elaeisis Delvare and LaSalle, 1993 (Hymenoptera: Eulophidae) in pupae of Zophobas confusa Gebien, 1906 (Coleoptera: Tenebrionidae) - Silva, Isabel Moreira da; Silva, Robson Oliveira; Andrade, Gilberto Santos; Zanuncio, José Cola; Pereira, Fabricio Fagundes; Pastori, Patrik Luiz (ENTOMOTROPICA, 2011)
Zophobas confusa Gebien, 1906 (Coleoptera: Tenebrionidae) es un nuevo hospedero alternativo para la cría masiva del parasitoide Palmistichus elaeisis Delvare and LaSalle, 1993 (Hymenoptera: Eulophidae) en el laboratorio